Proceedings of the 26th ACM International Conference on Multimedia 2018
DOI: 10.1145/3240508.3240665
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Cross-Media Retrieval with Soft-Smoothing

Abstract: Multimedia information have strong temporal correlations that shape the way modalities co-occur over time. In this paper we study the dynamic nature of multimedia and social-media information, where the temporal dimension emerges as a strong source of evidence for learning the temporal correlations across visual and textual modalities. So far, cross-media retrieval models, explored the correlations between different modalities (e.g. text and image) to learn a common subspace, in which semantically similar inst… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…In Uricchio et al [29], the value of temporal information for the tasks of image annotation and retrieval, such as tag frequency, is recognised. In order to model the temporal behaviour of data, embeddings must retain temporal correlations [2,9,15,24,27,38]. The challenge resides in capturing such correlations and incorporating them in cross-modal embeddings.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…In Uricchio et al [29], the value of temporal information for the tasks of image annotation and retrieval, such as tag frequency, is recognised. In order to model the temporal behaviour of data, embeddings must retain temporal correlations [2,9,15,24,27,38]. The challenge resides in capturing such correlations and incorporating them in cross-modal embeddings.…”
Section: Related Workmentioning
confidence: 99%
“…The focus has been on capturing correlations between instances (using category information when available), without accounting for temporal correlations, for data organisation. Recently, a temporal cross-modal common space approach was proposed [27], where temporal correlations are used to organise instances in a static embedding space. The authors observed that for dynamic data, the incorporation of temporal insights increases retrieval performance.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Modality projections into cross-modal subspaces must capture both inter-category and inter-modality correlations in that subspace. To this end, the cross-modal subspace learning problem is commonly formulated using a maximum-margin learning approach, by imposing a set of constraints over pairwise instance's similarity, on the target subspace [17,22,25,28,34].…”
Section: Adaptive Subspace Learningmentioning
confidence: 99%